The Role of Mindfulness in the Relationship of Anxiety and Resilience in Adolescents and Adults Post Covid-19 Pandemic - Widyaningrum, Hani; Mansoer, Winarini Wilman D (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The COVID-19 pandemic has had a profound effect on people's mental health. People are experiencing a variety of psychological issues because of the increase in COVID-19 cases, ranging from those connected to preventive actions and maintaining safety to the incidence of loss due to mortality caused by COVID-19. Excessive worry causes various changes in psychological functioning. Therefore, in dealing with unexpected conditions during the COVID-19 pandemic, positive psychology such as mindfulness is needed. Mindfulness is the state of being in which people bring their past experiences to the present moment with openness and acceptance. This can reduce anxiety caused by the COVID-19 pandemic and provide a high level of resilience to confront difficult times and adapt to the COVID-19 pandemic situation. The purpose of this study was to explore the role of mindfulness and its relationship between anxiety and resilience in adolescence and early adulthood. It was also to determine whether there is a significant association between mindfulness variables and anxiety, as well as mindfulness variables and resilience. The sample consisted of 74 respondents from West Java and DKI Jakarta aged 16 to 35 years old. Measurements in this study used the Connor-Davidson Resilience Scale (CD-RISC), Mindfulness Attention Awareness Scale (MAAS), and COVID-19 Anxiety Scale (CAS). The results found that there was a relationship between resilience and anxiety. There was a relationship between mindfulness and anxiety. However, there was no relationship between mindfulness and resilience. The conclusion might then be that mindfulness did not significantly moderate the relationship between anxiety and resilience.Pandemi Covid-19 telah membawa efek besar pada kesehatan mental masyarakat. Mengingat meningkatnya kasus Covid-19, manusia menghadapi segudang masalah psikologis, mulai dari terkait tindakan pencegahan dan menjaga keselamatan sampai terjadinya kehilangan akibat kematian yang disebabkan oleh Covid-19. Kekhawatiran yang berlebihan menyebabkan berbagai perubahan fungsi psikologis, maka dalam menghadapi kondisi yang tidak terduga selama masa pandemi Covid-19, dibutuhkan psikologi positif seperti mindfulness yaitu kondisi individu yang secara sadar membawa pengalamannya ke kondisi saat ini dengan penuh rasa keterbukaan dan rasa penerimaan, agar dapat mengurangi tingkat kecemasan akibat pandemi Covid-19 serta memiliki resiliensi yang tinggi untuk dapat menghadapi masa-masa sulit dan beradaptasi di situasi pandemi Covid-19. Penelitian ini bertujuan untuk mengeksplorasi peran mindfulness dan hubungannya antara kecemasan dan resiliensi pada usia remaja dan dewasa awal. Selain itu, untuk mengetahui apakah ada hubungan yang signifikan antara variabel mindfulness dengan kecemasan, dan variabel mindfulness dengan resiliensi. Sampel terdiri dari 74 responden dari Jawa Barat dan DKI Jakarta dengan rentang usia 16 sampai 35 tahun. Pengukuran dalam penelitian ini menggunakan Connor-Davidson Resilience Scale (CD-RISC), Mindfulness Attention Awareness Scale (MAAS), dan Covid-19 Anxiety Scale (CAS). Hasil ditemukan bahwa terdapat hubungan antara resiliensi dengan kecemasan, terdapat hubungan antara mindfulness dengan kecemasan, namun tidak terdapat hubungan antara mindfulness dengan resiliensi. Kemudian, mindfulness tidak signifikan memoderasi hubungan antara kecemasan dengan resiliensi.